Qualitative interviews to evaluate content validity of the ACTIV-2 COVID-19 Symptom Diary (ACSD) - Louis S. Matza; Katie D. Stewart; April N. Naegeli; Kayla M. Mills; Karin S. Coyne; Kara W. Chew; Michael D. Hughes; Davey M. Smith (SpringerOpen, 2023)
Plain English summary This study focused on the ACTIV-2 COVID-19 Symptom Diary (ACSD), a questionnaire that assesses symptom severity of COVID-19. The ACSD begins with global items assessing overall symptom severity, followed by a symptom checklist focusing on individual symptoms. Interviews were conducted with 30 adults who had tested positive for COVID-19. The patients reported their experiences with COVID-19, completed the ACSD, and provided their opinions about the ACSD. Based on input from these patients, the ACSD appears to be clear and easy to complete, and it includes the most common and important symptoms of COVID-19. The ACSD was edited for clarity, and "brain fog" and dizziness were recommended additions for future research. This study suggests that the ACSD is a useful questionnaire for assessment of COVID-19 symptoms in clinical studies. Studies like this are important for ensuring that symptoms are measured appropriately and accurately in clinical trials. Future research with larger samples will be needed to further examine the questionnaire.